XML Data Management : Native XML and XML-Enabled Database Systems - Chaudhri, Akmal; Rashid, Awais; Zicari, Roberto (Addison-Wesley Professional, 2003)
"This is an excellent book that combines a practical and analytical look at the subject." --Leo Korman, Principal Software Engineer, KANA Software As organizations begin to employ XML within their information-management and exchange strategies, data management issues pertaining to storage, retrieval, querying, indexing, and manipulation increasingly arise. Moreover, new information-modeling challenges also appear. XML Data Management --with its contributions from experts at the forefront of the XML field--addresses these key issues and challenges, offering insights into the advantages and drawbacks of various XML solutions, best practices for modeling information with XML, and developing custom, in-house solutions. In this book, you will find discussions on the newest native XML databases, along with information on working with XML-enabled relational database systems. In addition, XML Data Management thoroughly examines benchmarks and analysis techniques for performance of XML databases. Topics covered include: The power of good grammar and style in modeling information to alleviate the need for redundant domain knowledge Tamino's XML storage, indexing, querying, and data access features The features and APIs of open source eXist Berkeley DB XML's ability to store XML documents natively IBM's DB2 Universal Database and its support for XML applications Xperanto's method of addressing information integration requirements Oracle's XMLType for managing document centric XML documents Microsoft SQL Server 2000's support for exporting and importing XML data A generic architecture for storing XML documents in a relational database X007, XMach-1, XMark, and other benchmarks for evaluating XML database performance Numerous case studies demonstrate real-world problems, industry-tested solutions, and creative applications of XML data management solutions. Written for both XML and relational database professionals, XML Data Management provides a promising new approach to data management, one that is sure to positively impact the way organizations manage and exchange information. 0201844524B01302003.